Numerical Modelling of Liquid Ramjet Combustors - Thangadurai, G. Raja Singh; Chandran, B.S. Subhash; Babu, V.; Sundararajan, T. (Defence Science Journal, 2008)
The liquid fuel ramjet system employing a subsonic side-dump combustor is simulated inthe present study, and the predictions are compared with the available experimental data. Thecomplex combustion phenomenon in a ramjet combustor has been carried out using probabilitydensity function (PDF) approach. The complexity arises because of the mixing of fuel and airstreams, and the burning of the resultant mixture, within the confined space of the combustionchamber. The predicted numerical results have been validated with the results available in openliterature for a two-dimensional case and with in-house experimental data for a three-dimensionalcase. The methodology allows different designs to be evaluated quantitatively based on theperformance metrics such as combustion efficiency, flame stability, etc. Defence Science Journal, 2008, 58(1), pp.3-14, DOI:http://dx.doi.org/10.14429/dsj.58.1620